2022
DOI: 10.3389/fcvm.2022.876693
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Blocker Use in Older Hospitalized Patients Affected by Heart Failure and Chronic Obstructive Pulmonary Disease: An Italian Survey From the REPOSI Register

Abstract: Beta (β)-blockers (BB) are useful in reducing morbidity and mortality in patients with heart failure (HF) and concomitant chronic obstructive pulmonary disease (COPD). Nevertheless, the use of BBs could induce bronchoconstriction due to β2-blockade. For this reason, both the ESC and GOLD guidelines strongly suggest the use of selective β1-BB in patients with HF and COPD. However, low adherence to guidelines was observed in multiple clinical settings. The aim of the study was to investigate the BBs use in older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…For instance, a retrospective analysis of 4713 hospitalized patients with chronic kidney disease (CKD) aged ≥65 years reported that 21.9% were taking at least one inappropriate medication at the time of hospital admission, which was linked to multiple medication use and end-stage CKD [ 1 ]. Another study on patients with heart failure (HF) and chronic obstructive pulmonary disease (COPD) found a significant underuse of beta-blockers among older patients [ 2 ]. Moreover, the study identified cases of inappropriate prescribing of beta-blockers, including the use of contraindicated medications, affecting approximately 30% of patients with HF and COPD.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a retrospective analysis of 4713 hospitalized patients with chronic kidney disease (CKD) aged ≥65 years reported that 21.9% were taking at least one inappropriate medication at the time of hospital admission, which was linked to multiple medication use and end-stage CKD [ 1 ]. Another study on patients with heart failure (HF) and chronic obstructive pulmonary disease (COPD) found a significant underuse of beta-blockers among older patients [ 2 ]. Moreover, the study identified cases of inappropriate prescribing of beta-blockers, including the use of contraindicated medications, affecting approximately 30% of patients with HF and COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the clinical and pharmacological rationale suggesting the use of β-blockers in most patients with HF, it was reported that in hospitalized older patients (median age 82.8 years) affected by HF and COPD, only 36.9% were receiving a β-blocker on admission. This percentage became 38.0% at discharge, and there were no other β-blocker users after discharge [ 66 ]. These percentages were significantly lower than those observed in patients affected by HF alone (51.3 and 51.7%, respectively).…”
Section: The Pharmacological Treatment Of Copd In Older Adultsmentioning
confidence: 99%
“…Spontaneous reporting of suspected ADRs can create an agile and rapid system for identifying potential ADRs that have not yet been identified, known in pharmacovigilance as “signal generation”. This is of particular importance, especially in an ageing population, where the prevalence of multimorbidity (co-existence of two or more chronic conditions) and polypharmacy (the concomitant use of multiple medications) is continuously increasing, resulting in a higher risk of additional morbidity, potentially inappropriate medication, and drug-related adverse events [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The “signals” of potential drug-related side effects and adverse reactions can be further studied in depth by regulatory authorities, as well as the participation of notifiers [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%